The gender gap in sport performance: equity influences equality - Capranica, L.; Piacentini, M. F.; Halson, S.; Myburgh, K. H.; Ogasawara, E.; Millard-Stafford, M. L. (International Journal of Sports Physiology and Performance, 2013)
Sport is recognized as playing a relevant societal role to promote education, health, intercultural dialogue, and the individual development, regardless of an individual`s gender, race, age, ability, religion, political affiliation, sexual orientation, and socioeconomic background. Yet, it was not until the 2012 Summer Olympic Games in London that every country`s delegation included a female competitor. The gender gap in sport, although closing, remains, due to biological differences affecting performance, but it is also influenced by reduced opportunity and sociopolitical factors that influence full female participation across a range of sports around the world. Until the cultural environment is equitable, scientific discussion related to physiological differences using methods that examine progression in male and female world-record performances is limited. This commentary is intended to provide a forum to discuss issues underlying gender differences in sport performance from a global perspective and acknowledge the influence of cultural and sociopolitical factors that continue to ultimately affect female performance.